2003
DOI: 10.4049/jimmunol.171.3.1352
|View full text |Cite
|
Sign up to set email alerts
|

Positive Modulation of IL-12 Signaling by Sphingosine Kinase 2 Associating with the IL-12 Receptor β1 Cytoplasmic Region

Abstract: IL-12 is a key immunoregulatory cytokine that promotes Th1 differentiation and cell-mediated immune responses. IL-12 stimulation results in the activation of Janus kinase 2 and tyrosine kinase 2 and, subsequently, STAT4 and STAT3. In addition, mitogen-activated protein kinase kinase 6/p38 mitogen-activated protein kinase and phosphatidylinositol 3-kinase/Akt pathways have been recently demonstrated to be activated by IL-12 and play an important role in IL-12 signaling. To further elucidate the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 50 publications
4
58
0
Order By: Relevance
“…However, we found that mutation of the conserved leucine in the SphK2 BH3 domain did not abolish its localization to the ER, suggesting that its putative transmembrane domains might also contribute to its association with internal membranes. Alternatively, SphK2 may interact with other membrane proteins (37). Consistent with the notion that localization of SphK2 to the ER and internal membranes is important for its function, targeting cytosolic SphK1, but not catalytically inactive SphK1, to the ER converted it from anti-apoptotic to pro-apoptotic.…”
Section: Dihydro-sphsupporting
confidence: 53%
See 2 more Smart Citations
“…However, we found that mutation of the conserved leucine in the SphK2 BH3 domain did not abolish its localization to the ER, suggesting that its putative transmembrane domains might also contribute to its association with internal membranes. Alternatively, SphK2 may interact with other membrane proteins (37). Consistent with the notion that localization of SphK2 to the ER and internal membranes is important for its function, targeting cytosolic SphK1, but not catalytically inactive SphK1, to the ER converted it from anti-apoptotic to pro-apoptotic.…”
Section: Dihydro-sphsupporting
confidence: 53%
“…Igarashi and co-workers (27) reported that when SphK2 was transiently expressed in HeLa and COS7 cells, it was localized in the nuclei, whereas in HEK 293 cells it was localized to the cytosol. In contrast, overexpressed SphK2 was found to associate with the interleukin-12 receptor-␤1 at the plasma membrane in HEK 293 cells and T cell hybridomas (37). However, using a specific antibody, we …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Cells were lysed in a lysis buffer containing protease inhibitors, and resultant cell lysates were separated on an SDS-PAGE under reducing conditions and transferred to polyvinylidene difluoride membrane (Millipore) as described previously (31). The membrane was then blocked, probed with primary Ab and then with appropriate secondary Ab conjugated to HRP, and visualized with the ECL detection system (Amersham Biosciences) according to the manufacturer's instructions.…”
Section: Western Blottingmentioning
confidence: 99%
“…The SphFl concentrations used were 2. 5,5,10,15,20,30,40, and 60 μM, using 2% fatty-acid free BSA as a carrier for SphFl. The K M and V max were determined assuming Michaelis-Menten kinetics and fitting the data points in Origin (OriginLab Corporation, Northampton, MA).…”
mentioning
confidence: 99%